THU0386 Use of biologics and nsaids in treating patients with axial spondyloarthritis in the us-based corrona psoriatic arthritis/spondyloarthritis (PSA/SPA) registry. (15th June 2017) - Mease, PJ; Heijde, D van der; Karki, C; Liu, M; Pandurengan, R; Park, Y; Greenberg, JD
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease affecting the sacroiliac joints and spine. Treatment primarily consists of first-line nonsteroidal anti-inflammatory drugs (NSAIDs) and/or biologic therapy when disease activity persists despite NSAID therapy. Although many studies have evaluated the efficacy of these treatments, there are few studies that have characterized NSAIDs and/or biologic therapy among patients with axSpA in the United States. Objectives: To characterize patients with axSpA treated with NSAIDs only, biologics only, or both NSAIDs and biologics at the time of enrollment in the US-based Corrona PsA/SpA Registry. Methods: This study included all patients with axSpA diagnosed by the rheumatologist aged ≥18 years enrolled in the Corrona Registry between March 2013 and September 2016 who were treated with NSAIDs only, biologics only, or both NSAIDs and biologics at the time of enrollment (baseline). Patients fulfilled the Assessment of SpondyloArthritis international Society classification criteria. 1 Demographics, clinical characteristics, disease activity measures and treatment history were collected at enrollment and described for each group. Results: As of September 2016, 359 patients with axSpA met the study inclusion criteria; at baseline, 224 patients (62.4%) were receiving NSAIDs (92 [25.6%] with NSAIDs only and 132 [36.8%] with both NSAIDs and biologics) and 135 patients (37.6%) were receiving biologics only. Baseline characteristics were similar across all treatment subgroups with regards to age, race and body mass index. Fewer females were treated with biologics (with/without NSAIDs) compared to the NSAIDs only group. At baseline, patients treated with NSAIDs or both NSAIDs and biologics were older, had longer duration of disease with worse disease activity (measured by ASDAS and BASDAI), functional impairment (BASFI and HAQ-DI) and had worse pain and fatigue compared to those treated with biologics only (Table 1 ). 88–96% of patients receiving biologics (with or without NSAIDs) had prior biologic use compared to only 25% of NSAIDs only group. Patients treated with biologics only reported decreased percentage of impairment while working, overall work impairment and activity impairment at baseline compared with patients treated with NSAIDs only and both NSAIDs and biologics. Conclusions: About two-thirds of patients with axSpA were treated with NSAIDs (with or without biologics) and about three-fourths of patients were treated with biologics (with or without NSAIDs) at enrollment. Patients that were already treated with biologics without NSAIDs at enrollment showed better measures of disease activity and PROs compared with the other treatment groups. Future research will assess changes in clinical and disease characteristics over time by treatment subgroup. References: Rudwaleit M, et al. Ann Rheum Dis. 2009;68(6):777–783. Acknowledgements: Corrona, LLC, has been supported through contracted subscriptions in the last 2 years by AbbVie, Amgen, BMS, Crescendo, Eli Lilly and Company, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. Disclosure of Interest: P. Mease Grant/research support from: Celgene, Novartis, AbbVie, Amgen, BMS, Lilly, Pfizer, UCB, Consultant for: Celgene, Corrona, Novartis, AbbVie, Amgen, BMS, Crescendo, Genentech, Janssen, Lilly, Merck, Pfizer, UCB, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Daiichi, Eli Lilly, Galapagos, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi Aventis and UCB, Employee of: Imaging Rheumatology BV, C. Karki Employee of: Corrona, LLC, M. Liu Employee of: Corrona, LLC, R. Pandurengan Employee of: Corrona, LLC, Y. Park Employee of: Novartis, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: Lilly, Genentech, Janssen, Novartis, Pfizer, Employee of: Corrona, LLC